2013
DOI: 10.1371/journal.ppat.1003596
|View full text |Cite
|
Sign up to set email alerts
|

Midcell Recruitment of the DNA Uptake and Virulence Nuclease, EndA, for Pneumococcal Transformation

Abstract: Genetic transformation, in which cells internalize exogenous DNA and integrate it into their chromosome, is widespread in the bacterial kingdom. It involves a specialized membrane-associated machinery for binding double-stranded (ds) DNA and uptake of single-stranded (ss) fragments. In the human pathogen Streptococcus pneumoniae, this machinery is specifically assembled at competence. The EndA nuclease, a constitutively expressed virulence factor, is recruited during competence to play the key role of converti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
87
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 50 publications
(72 reference statements)
4
87
0
Order By: Relevance
“…To identify the genetic basis for the lack of transformability in the 11 nontransformable isolates, we performed DNA sequencing analysis of 24 pneumococcal genes that are required for natural transformation, including endA and the 23 essential com genes (24,25). This analysis revealed that five of the nontransformable isolates (TH880, TH2813, TH2861, TH2863, and TH2893) harbored potential loss-of-function mutations and unique nucleotide polymorphisms in the coding sequences of one or more essential com genes ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify the genetic basis for the lack of transformability in the 11 nontransformable isolates, we performed DNA sequencing analysis of 24 pneumococcal genes that are required for natural transformation, including endA and the 23 essential com genes (24,25). This analysis revealed that five of the nontransformable isolates (TH880, TH2813, TH2861, TH2863, and TH2893) harbored potential loss-of-function mutations and unique nucleotide polymorphisms in the coding sequences of one or more essential com genes ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Many of the late com genes are involved in binding, processing, uptake, and recombination of foreign DNA (19,20). Although a previous study identified 124 genes in strain TIGR4 that are induced by CSP treatment (23), only 23 of the CSP-inducible genes are essential for natural transformation (24,25). Finally, the constitutively expressed gene endA, coding for a nuclease, is also required for DNA uptake (25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cyan fluorescent protein ( CFP) construct Using a previously described genetic markerless insertion system, 45 a codon-optimized CFP sequence recently reported by Berg e et al 46 to be stable in Gram positive cocci was inserted into the chromosome of E. faecalis OG1RF under constitutive expression using the lactococcal P23 promoter system 47 creating OG1RF::p23 cfp (OG1RF cfp C ). From a series of CFP-expressing transconjugants, mutants were empirically screened by IFM to select those with the best combination of fluorescent intensity, stability, and resistance to photobleaching; candidates were checked for basic metabolic and phenotypic growth to ensure no significant differences from parental strain prior to general experimental use.…”
Section: Strains and Plasmidsmentioning
confidence: 99%
“…Recently, improved fluorescent reporter proteins, and highly sensitive and specific reagents for fluorescent staining were used to demonstrate localization of the competence machinery and visualize individual genetic transformation events in Streptococcus pneumoniae . (46). Similar approaches hold great promise for analysis of plasmid copy number and conjugation in enterococci and staphylococci growing in biofilms.…”
Section: Resultsmentioning
confidence: 99%